Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-23T20:29:25+01:00
1) Développement:

E= 3(2a-1) - (2a-1) (2a+1)
E= 6a -3 - (4a² +2a -2a -1)
E= 6a -3 -4a² +1
E= -4a² +6a -2

2) Calcul pour a=2:

E= -4a² +6a -2
E= -4*2² +6*2 -2
E= -16 +12 -2
E= -18 +12
E= -6

3) Factorisation:

E= 3 (2a -1) - (2a-1) (2a+1)
E= (2a-1) (1 -2a -1)
E= (2a-1) (-2a)
E= -2a (2a-1)

4) Résolution:

(2a-1) (2-2a) = 0
Règle du produit nul:
2a-1 = 0  ou  2-2a = 0
2a = 1     ou    -2a = -2
a= 1/2     ou       a= 1

Voilà ! J'espère t'avoir aidé(e) ! :)
2014-03-23T21:18:31+01:00
1. E=3(2a - 1)- (2a - 1) (2a + 1)
E= (2a - 1) ( 3 - 2a - 1)
E= (2a - 1) (2 - 2a)
E= 4a - 2 + 2a
E= 6a - 2
2. E= 6a -2 
E= (6 x 2) - 2
E= 10
3. E= 6a- 2
E= (  \sqrt{6a} - \sqrt{2} ) {2}